Penerapan Video Based Learning Gizi Seimbang Terhadap Pengetahuan Difabel Tunarungu Di Sekolah Luar Biasa (SLB) Negeri Pati, Jawa Tengah - Putri, Sheilla Eka; Soeyono, Rahayu Dewi (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Deaf children are children who have hearing loss so they cannot hear sounds perfectly. In deaf children, everything that is recorded through visual perception is only like a silent movie. Learning video is one of the media that can be used in learning to listen, imitate and distinguish. Learning video media is expected to help deaf students improve their abilities in learning and students are not easily bored. This study aims to determine the effect of providing video-based education on the knowledge of deaf people. This research is a quantitative research using pre-experimental method. The planning used was One Group Pre-Test and Post-Test Design with a sample of 15 deaf students at SLB Negeri Pati. The results showed that there was an effect of providing balanced nutrition education on the knowledge of the Deaf using video media as evidenced by the results of the Paired T-Test statistical test with Sig. 0,0004 (<0,05). In addition, the results also show that there is a relationship between the provision of balanced nutrition education on the attitude (affective) of the Deaf using video media as evidenced by the results of the Wilcoxon statistical test with Sig. 0,038 (<0,05).